Barriers Faced By Nurses In Providing Patient Education In Saudi Hospitals (The Review of Diabetic Studies, 2024)
Introduction: Patient education is one of the core nursing interventions that have a great impact on clinical outcomes and lower hospital readmission rates. The problem of rising trends of chronic illnesses such as diabetes and hypertension in the Kingdom of Saudi Arabia (KSA), together with the healthcare objectives of the Vision 2030, creates an urgent need among nurses to deliver effective health instruction. This process is however usually hampered by several organization and cultural factors.Objective: This systematic review has been developed to determine the multi-faceted elements that hinder nurses from supplying successful patient education in a clinical setting in Saudi Arabia.Method: A systematic review was done in accordance with PRISMA. Peer-reviewed articles published in 2015-2025 were searched in electronic databases, such as PubMed, CINAHL, ScienceDirect, and the Saudi Medical Journal. Eligibility criteria included original research (qualitative, quantitative, and mixed-methods) that included registered nurses, who worked in Saudi hospitals. The thematic analysis was performed by a standardized form to extract the data and analyzed them using thematic synthesis.Conclusion: audi nurses are struggling with a special triple barrier of workload, language, and culture. These limitations often lead to neglecting patient education, even though it is clear that technical nursing care has a higher priority. To realize the Vision 2030 goals, the hospital administrators will have to institutionalize the concept of the so-called protected time to teach and use the digital and bilingual tools to overcome the language barrier between the expatriate workers and the local patients.